Multiagent Chemotherapy Followed by Stereotactic Body Radiotherapy Versus Conventional Radiotherapy for Resected Pancreas Cancer. (21st November 2022) - Mokhtech, Meriem; Miccio, Joseph A.; Johung, Kimberly; Cecchini, Michael; Stein, Stacey; Narang, Amol K.; Herman, Joseph M.; Kunstman, John; Haddock, Michael G.; Anker, Christopher J.; Jabbour, Salma; Hallemeier, Christopher L.; et al.
Abstract : Background and Purpose: Chemotherapy followed by margin-negative resection (R0) is the treatment of choice for patients with localized pancreatic ductal adenocarcinoma (PDAC). Neoadjuvant multiagent chemotherapy (MAC) or MAC then radiotherapy (RT) may optimize surgical candidacy. The purpose of this study was to compare pathologic outcomes of MAC followed by conventionally fractionated radiotherapy (CRT) versus stereotactic body radiotherapy (SBRT) for patients with resected PDAC. Methods: Patients diagnosed with nonmetastatic PDAC between 2012 and 2017 and who received preoperative MAC or MAC+RT were identified in the National Cancer Database. Variables associated with R0 and overall survival were identified with logistic regression and Cox analysis ( P <0.05). Results: A total of 5273 patients were identified (MAC: 3900, MAC+CRT: 955, MAC+SBRT: 418). The median RT dose/fraction (fx) in the MAC+CRT and MAC+SBRT cohorts was 50.4 Gy/28 fx and 33 Gy/5 fx. Patients receiving MAC+CRT versus MAC+SBRT had similar rates of ypT3-T4 disease (54% vs. 58%, P =0.187), R0 (87% vs. 84%, P =0.168), and pathologic complete response (pathologic complete response; 6% vs. 4%, P =0.052), however, MAC+CRT was associated with less regional lymphatic disease (ypN+: 28% vs. 41%, P <0.001). The median overall survival of patients receiving MAC+CRT versus MAC+SBRT was 24.6 versus 29.5 months ( P =0.045). Conclusions: For patients with resected PDAC, MAC+CRT, and MAC+SBRT had similar rates of R0 and pathologic complete response, although MAC+CRT was associated with lower ypN+. Prospective evaluation of neoadjuvant RT regimens with attention to radiation therapy design is warranted.